Comparing survival outcomes of localized tumor destruction, sublobar resection, and pulmonary lobectomy in stage IA non-small cell lung cancer: a study from the SEER database - Lin Cheng; Sheng-Wei Li; Xiao-Guang Li (European Journal of Medical Research)
Abstract Purpose A large-scale comparative analysis was performed with the aim of comparing local tumor destruction (LTD), sublobar resection (SR), and pulmonary lobectomy (PL) for cancer-specific survival (CSS) and overall survival (OS) in stage IA non-small cell lung cancer (NSCLC). Methods In the Surveillance, Epidemiology, and End Results (SEER) database (2000–2021), we included patients with pathologically confirmed stage IA non-small cell lung cancer who were treated with LTD, SR, or PL. Comparison between groups was performed separately after 1:1 proportional propensity score matching (PSM) with a caliper value of 0.1. Kaplan–Meier analysis was performed to compare survival outcomes between groups. Results In the total cohort of 4437 LTD patients, 2425 SR patients, and 6386 PL patients, 84.18% of LTD-treated patients were older than 65 years, whereas 68.95% of SR-treated patients and 62.82% of PL-treated patients were older than 65 years. The CSS (HR = 0.756, 95% CI 0.398 ~ 1.436, P = 0.393) and OS (HR = 0.46, 95% CI 0.553 ~ 1.295, P = 0.442) of LTD were consistent with SR. Whereas LTD demonstrated lower CSS (HR = 0.603, 95% CI 0.378 ~ 0.940, P = 0.024) and OS (HR = 0.590, 95% CI 0.432 ~ 0.805, P < 0.001) than PL, but were consistent when the tumor size was ≤ 1 cm. The CSS (HR = 1.215, 95% CI 0.872 ~ 1.693, P = 0.249) of SR was consistent with PL, but OS (HR = 1.347, 95% CI 1.079 ~ 1.681, P = 0.008) was higher than PL, but were consistent when the tumor size was 1.1–3 cm. Conclusions In patients with stage IA non-small cell lung cancer, the CSS and OS of LTD were no worse than those of SR. Compared with PL, the CSS and OS of LTD were lower, but when the tumor size was ≤ 1 cm, the CSS and OS of LTD were no worse than those of PL.